IMPLEMENTASI CSR (CORPORATE SOCIAL RESPONSIBILITY) PT. SEMEN BATURAJA (Persero) Tbk SEBAGAI UPAYA DALAM PEMBINAAN LINGKUNGAN DAN KEMITRAAN - Ardi Cahya, Riyan (JIM : Journal Of International Management, 2022)
Industry is a sector that plays an important role in the development of the region and the income of the people. Predominant on the basis of agriculture is the industrial sector, the government's view of industrialization. At least as the engine of economic development, it is often seen as the gateway to leading a society to prosperity. Governments help strengthen the environment through corporate social responsibility, known as corporate social responsibility (CSR). Corporate Social Responsibility (CSR) can be used as an alternative that should be developed to share the direction of corporate responsibility for various social and environmental issues. CSR can be used as a strategy for companies to stand up for their communities and the environment, and as a form of action to maintain and counter the potential for negative access to industrialization. However, a significant number of businesses within the community have mostly negative impacts despite their welfare and development benefitsThis company has been operating in Sukajadi Village for a long time and does not neglect the concept of CSR. How about implementing CSR (Corporate Social Responsibility) Reducing Impacts of Environmental Damage.